The past is a grotesque animal. Ideologies of urban memory in post-socialist Belgrade (REVISTA NODO, 2022)
This essay arises from the vision of some monumental ruins of the buildings of extinct Yugoslavia, in Belgrade, capital of the Republic of Serbia. Those buildings, bombed in 1999 by NATO forces, commanded by the U.S.A, are still not rebuilt or demolished, two decades after the events. Ruins like the Generalštab (Yugoslav General Staff Building) on the diplomatic Kneza Milosa Avenue, generate a great public controversy about their fate. This situation serves as a trigger for a series of reflections on the recent history of Yugoslavia and the urbicidal component of the Balkan wars. It also opens the door to question the ideological springs in the construction of collective memory. In the case of post-socialist Belgrade, the ruins have been used propagandistically for nationalist victimization; however, paradoxically, they also lead to uncomfortable questions for the Serbian authorities. Questions about the past and about the future. The essay analyzes some important events in the urban planning of socialist Belgrade and the power of those projects as a “concrete utopia”. I also compare those urban milestones with the current situation. Not less important is, that this essay is a tribute to the figure of Bogdan Bogdanović, Serbian architect and last mayor of Socialist Belgrade, one of the last urban utopians of the 20th century.
Keywords: post-socialist studies; collective memory; yugoslav modernism; architectural heritage; urban ruins